Analysis of the Dose Drop at the Edge of the Target Area in Heavy Ion Radiotherapy. (11th November 2021) - Ma, Xiaoyun; Zhang, Mengling; Meng, Wanbin; Lu, Xiaoli; Wang, Ziheng; Zhang, Yanshan
Abstract : Background . The dose distribution of heavy ions at the edge of the target region will have a steep decay during radiotherapy, which can better protect the surrounding organs at risk. Objective . To analyze the dose decay gradient at the back edge of the target region during heavy ion radiotherapy. Methods . Treatment planning system (TPS) was employed to analyze the dose decay at the edge of the beam under different incident modes and multiple dose segmentation conditions during fixed beam irradiation. The dose decay data of each plan was collected based on the position where the rear edge of the beam began to fall rapidly. Uniform scanning mode was selected in heavy ion TPS. Dose decay curves under different beam setup modes were drawn and compared. Results . The dose decay data analysis showed that in the case of single beam irradiation, the posterior edge of the beam was 5 mm away, and the posterior dose could drop to about 20%. While irradiation in opposite direction, the posterior edge of the beam was 5 mm away, and the dose could drop to about 50%. In orthogonal irradiation of two beams, the posterior edge of the beam could drop to about 30-38% in a distance of 5 mm. Through the data analysis in the TPS, the sharpness of the dose at the back edge of the heavy ion beam is better than that at the lateral edge, but the generated X-ray contamination cannot be ignored. Conclusions . The effect of uneven CT value on the dose decay of heavy ion beam should also be considered in clinical treatment.